Genomic Landscape of High‐Altitude Adaptation in East African Mountain Honey Bees (Apis mellifera) - Marco Mazzoni; Florian Loidolt; Sonja Kersten; Deborah Ruth Amulen; Patrick Vudriko; Philipp Meyer; Victor Sebastian Scharnhorst; Ricarda Scheiner; Martin Hasselmann (Ecology and Evolution)
ABSTRACT Understanding the evolutionary processes leading to differentiation within species is a central goal in population biology. A key process is local adaptation, for which organisms evolve traits enhancing the survival and reproduction in specific environments. Honey bees (Apis mellifera) in East Africa are well adapted to highland environments, showing different phenotypes, including behavior, compared to lowland bees. Despite these differences, highland and lowland honey bees show very low genetic differentiation, with the exception of two segments on chromosome 7 (r7) and chromosome 9 (r9), which were previously identified as chromosomal inversions. These inversions are rare in lowland populations, suggesting a key role in adaptation to high‐elevation habitats. In this study, we obtained 24 whole genomes from honey bees of Western Uganda and compared these with existing data from Kenya. We show that the chromosomal inversions play a pivotal role in local adaptation in both regions but with substantial differentiation. Genome‐wide analysis of polymorphism revealed additional genomic regions potentially involved in high‐altitude adaptation. The acquisition of transcriptome data from highland and lowland honey bees in Uganda has enabled the first insights into the differential expression of genes between these bees. Our findings elucidate the involvement of genes in behavioral and oxygen consumption processes. This paves the way to clarify the interplay of r7 and r9 with gene expression and to unravel the regulatory network underlying A. mellifera adaptation to high‐elevation habitats. Our study will contribute to a better understanding of the evolutionary processes in honey bee populations driven by environmental conditions.